High-dimensional mass cytometry analysis of NK cell alterations in AML identifies a subgroup with adverse clinical outcome - Chretien, Anne-Sophie; Devillier, Raynier; Granjeaud, Samuel; Cordier, Charlotte; Demerle, Clemence; Salem, Nassim; Wlosik, Julia; Orlanducci, Florence; Gorvel, Laurent; Fattori, Stephane; Hospital, Marie-Anne; Pakradouni, Jihane; et al. (Proceedings of the National Academy of Sciences - PNAS, 2021)
Natural killer (NK) cells are major antileukemic immune effectors. Leukemic blasts have a negative impact on NK cell function and promote the emergence of phenotypically and functionally impaired NK cells. In the current work, we highlight an accumulation of CD56⁻CD16⁺ unconventional NK cells in acute myeloid leukemia (AML), an aberrant subset initially described as being elevated in patients chronically infectedwith HIV-1. Deep phenotyping of NK cells was performed using peripheral blood from patients with newly diagnosed AML (n = 48, HEMATOBIO cohort, NCT02320656) and healthy subjects (n = 18) by mass cytometry. We showed evidence of amoderate to drastic accumulation of CD56⁻CD16⁺ unconventional NK cells in 27% of patients. These NK cells displayed decreased expression of NKG2A as well as the triggering receptors NKp30 and NKp46, in line with previous observations in HIV-infected patients. High-dimensional characterization of these NK cells highlighted a decreased expression of three additional major triggering receptors required for NK cell activation, NKG2D, DNAM-1, and CD96. A high proportion of CD56⁻CD16⁺ NK cells at diagnosis was associated with an adverse clinical outcome and decreased overall survival (HR = 0.13; P = 0.0002) and event-free survival (HR = 0.33; P = 0.018) and retained statistical significance in multivariate analysis. Pseudotime analysis of the NK cell compartment highlighted a disruption of the maturation process, with a bifurcation from conventional NK cells toward CD56⁻CD16⁺ NK cells. Overall, our data suggest that the accumulation of CD56⁻CD16⁺ NK cells may be the consequence of immune escape from innate immunity during AML progression.